Magic and Discredit in the Merovingian Court: The Case of Fredegunda - Jiménez Sánchez, Juan Antonio; Seijo Ibáñez, Elisabet (Gerión. Revista de Historia Antigua, 2020)
Our present research focuses on the use of the accusation of practising magic to defame Queen Fredegunda of Neustria (547-597), one of the most charismatic personalities of Merovingian’s history. That accusation was an effective way to relegate someone to the realm of alterity and marginality. Fredegunda was accused of resorting to magical remedies in order to keep herself in power and dispose of her political opponents, whereas in other occasions, paradoxically, she is presented as an active and bloody pursuer of witchcraft. The author of almost all the news related to this issue is Gregory of Tours, who in his Historiae never missed an opportunity to charge against her.
Keywords: Gregory of Tours; Franks; Defamation; Sorcery; Poison